Zeitgenössische jüdische Autobiographie - Miething, Christoph (Romania Judaica, 2011)
The proceedings of the conference of the same name assemble papers concentrating largely on Franco-Jewish autobiography in the last few decades. Relevant literature in English and German is also discussed. In addition, three Italian authors of autobiographies comment on their own works. The theoretical reflection undertaken in the volume either accompanies the analysis of individual works or takes a broader view. It centres (a) on the relationship between autobiography and 'auto-fiction', and (b) on the fundamental issue of what we precisely mean when we speak of 'Jewish autobiographies'.